Food Plants of 19 butterflies species (Lepidoptera) from Loreto, Peru - Vásquez Bardales, Joel (2017)
This work reports the food plants utilized by 19 species of butterflies from Allpahuayo-Mishana Research Center and the Community of San Rafael, Loreto, Peru. We report 23 plant species and one hybrid of angiosperms used by the butterflies. Larval host plants were 21 species and five were adult nectar sources. Two species were both host plant and nectar source: Passiflora coccinea Aubl. and Passiflora edulis Sims. The most frequently used plant families were Solanaceae, Passifloraceae, Fabaceae and Aristolochiaceae.